A survey on tomato leaf grey spot in the two main production areas of Argentina led to the isolation of Stemphylium lycopersici representatives which were genetically diverse and differed in their virulence - Franco, Mario Emilio Ernesto (2017)
Tomato gray leaf spot was first reported in Argentina in 1990. Since then, the disease has not only increased in endemic areas, but also disseminated in other tomato-growing areas. In a survey of plants with typical symptoms of Tomato grey leaf spot disease we isolated 27 Stemphylium representatives from the two main tomato-growing areas of Argentina. Cultural features such as sporulation, conidia morphometry among others revealed high variability between isolates, which was confirmed by Inter Simple Sequence Repeat (ISSR)-PCR technique. A molecular phylogenetic analysis comprising the Internal Transcribed Spacer (ITS) and the glyceraldehyde-3-phosphate dehydrogenase (gpd) gene partial sequences unambiguously identified all isolates as Stemphylium lycopersici. Based on disease severity on detached leaves, isolates were grouped in three categories (high, medium and low virulent). No correlation was found between phenotypic or genotypic characters and the geographical origin of the isolates.